Induction of Apoptosis in Hepatocellular Carcinoma Cell Lines by Novel Indolylacrylamide Derivatives: Synthesis and Biological Evaluation. Issue 5 (14th April 2021) - Hawash, Mohammed; Kahraman, Deniz Cansen; Cetin‐Atalay, Rengul; Baytas, Sultan Nacak
Abstract: Hepatocellular carcinoma (HCC) is the most prevalent primary liver cancer and one of the leading causes of cancer associated death worldwide. This is due to the highly resistant nature of this malignancy and the lack of effective treatment options for advanced stage HCC patients. The hyperactivity of PI3K/Akt and Ras/Raf/MEK/ERK signaling pathways contribute to the cancer progression, survival, motility, and resistance mechanisms, and the interaction of these two pathways are responsible for the regulation of cancer cell growth and development. Therefore, it is vital to design and develop novel therapeutic options for HCC treatment targeting these hyperactive pathways. For this purpose, novel series of trans‐ indole‐3‐ylacrylamide derivatives originated from the lead compound, 3‐(1 H ‐indole‐3‐yl)‐ N ‐(3, 4, 5‐trimethoxyphenyl)acrylamide, have been synthesized and analyzed for their bioactivity on cancer cells along with the lead compound. Based on the initial screening, the most potent compounds were selected to elucidate their effects on cellular signaling activity of HCC cell lines. Cell cycle analysis, immunofluorescence, and Western blot analysis revealed that lead compound and ( E )‐ N ‐(4‐ tert ‐butylphenyl)‐3‐(1 H ‐indole‐3‐yl)acrylamide induced cell cycle arrest at the G2/M phase, enhanced chromatin condensation and PARP‐cleavage, addressing induction of apoptotic cell death. Additionally, these compounds decreased the activity of ERK signaling pathway, where phosphorylated ERK1/2 and c‐Jun protein levels diminished significantly. Relevant to these findings, the lead compound was able to inhibit tubulin polymerization as well. To conclude, the novel trans‐ indole‐3‐ylacrylamide derivatives inhibit one of the critical pathways associated with HCC which results in cell cycle arrest and apoptosis in HCC cell lines. Abstract :